2020
DOI: 10.1084/jem.20191220
|View full text |Cite
|
Sign up to set email alerts
|

Early type I IFN blockade improves the efficacy of viral vaccines

Abstract: Type I interferons (IFN-I) are a major antiviral defense and are critical for the activation of the adaptive immune system. However, early viral clearance by IFN-I could limit antigen availability, which could in turn impinge upon the priming of the adaptive immune system. In this study, we hypothesized that transient IFN-I blockade could increase antigen presentation after acute viral infection. To test this hypothesis, we infected mice with viruses coadministered with a single dose of IFN-I receptor–blocking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 65 publications
(87 reference statements)
5
54
0
Order By: Relevance
“…Some CCHFV experimental vaccines have shown efficacy in type I IFN-deficient mice after a single-dose 13,20,21 . However, our immunogenicity data certainly indicate that the third vaccination may not be needed and the use of immunodeficient mice may not strictly predict efficacy in immunocompetent non-human primates and humans 43,44 . Second, our study design of performing a timed necropsy on day 6 PI was chosen to maximize readout parameters but it prevented us from evaluating the possibility of delayed disease development in sham and NP + GPC vaccinated animals.…”
Section: Discussionmentioning
confidence: 95%
“…Some CCHFV experimental vaccines have shown efficacy in type I IFN-deficient mice after a single-dose 13,20,21 . However, our immunogenicity data certainly indicate that the third vaccination may not be needed and the use of immunodeficient mice may not strictly predict efficacy in immunocompetent non-human primates and humans 43,44 . Second, our study design of performing a timed necropsy on day 6 PI was chosen to maximize readout parameters but it prevented us from evaluating the possibility of delayed disease development in sham and NP + GPC vaccinated animals.…”
Section: Discussionmentioning
confidence: 95%
“…This earlier study showed that CD8 T cells primed at the early stage of the infection preferentially differentiate into Tem, whereas CD8 T cells primed during the end of the infection preferentially differentiate into Tcm. Furthermore, we have previously shown that protracted acute infections favor Tem differentiation ( 13 ). Altogether, these prior reports suggest that a protracted antigen stimulation after a prime imprints a Tem phenotype, whereas a shortened antigen stimulation after a prime imprints a Tcm phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Binding antibody titers were measured using ELISA as described previously ( 18 , 19 ), but using spike protein instead of viral lysates. In brief, 96-well flat bottom plates MaxiSorp (Thermo Scientific) were coated with 0.1μg/well of the respective spike protein, for 48 hr at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Binding antibody titers were quantified using ELISA as described previously 33,34 , using spike protein as a coating antigen. In brief, 96-well flat bottom plates MaxiSorp (Thermo Scientific) were coated with 0.1μg/well of SARS CoV-2 RBD protein, for 48 hr at 4°C.…”
Section: Methodsmentioning
confidence: 99%